Managing heritage language relevance and language revitalisation: The case of Malacca Portuguese creole / Soh Wen Yi - Soh, Wen Yi (2015)

(untitled)
This thesis is set against the backdrop of the wider multilingual and postcolonial context and local language revitalisation efforts. The language in study, Malacca Portuguese Creole (MPC), is a Portuguese-based contact language undergoing language shift, spoken as heritage language by a concentrated population of approximately 800 people (Baxter, 2013) in the main research site, Portuguese Settlement (PS), Malacca, West Malaysia. The development of MPC and people identifying with MPC as their heritage language can be traced to the arrival of Portuguese in Malacca in 1511. The bottom-up research design of this thesis is drawn from Constructivist Grounded Theory (Charmaz, 2006, 2014). To understand and explain gaps between views and actions (initially driven by a perceived gap between language revitalisation efforts and reactions towards efforts) and as guided by questions and leads from emerging concepts and categories, the purpose and focus of research were redirected from a general investigation into MPC language revitalisation to capturing the experience, expressivity and dynamics of PS MPC-speaking group members, as illuminated by the language revitalisation process. The initial data collection employed interviewing as the main research instrument. Research participants were MPC speakers involved in revitalisation efforts and those who would be recipients of efforts. The research process was iterative as researcher moved between research procedures including data collection, coding, constant comparative method, memo-writing and theoretical sampling; analysis and conceptualisation were simultaneous. Theoretical sampling, the second phase of data collection according to theoretical relevance, proceeded by contacting research participants, analysing survey, examination of writings in and about MPC and its speakers and using literature as data. This thesis proposes a substantive model which brings the dynamics and voices of a contact-language-speaking group to the forefront. The core iv category of the model, managing relevance of heritage language, can be related to the basic social process of coping mechanisms in response to social development, in the quest of a basic social process or central phenomenon as pursued in a Grounded Theory study. It refers to the process of keeping one’s heritage language relevant as an aspect of one’s social life while maintaining other parts of social life and self-identifications. MPC-speaking group members who have initiated language revitalisation efforts have been motivated to take things into their own hands, showing their coping mechanisms more explicitly, in comparison with non-language-revitalisation-actors whose coping strategies are less explicit. The process of managing heritage language relevance helps construct a particular sense of self: a self identifying with a MPC-speaking heritage; this forms the socio-psychological and emotional dimension of the process. To understand this self-managing dimension and because self-constructing is not an isolated process, a socio-historical or socio-cultural dimension enters the picture. This new way of looking at the dynamics of a contact-language-speaking group in managing heritage language relevance can be applied to promote, plan and integrate the relevance of heritage language in future language revitalisation efforts. The present study is the first in employing Grounded Theory to conduct a formal research on MPC and the first to explore the MPC language revitalisation process cycle.